Pursuing performance and maintaining compliance: Balancing performance improvement and accountability in Ontario's public health system. (June 2016) - Price, Alex; Schwartz, Robert; Cohen, Joanna; Scott, Fran; Manson, Heather
Abstract: This article examines the compatibility between performance improvement and compliance‐based accountability in the implementation of a new system of public health performance management in Ontario. Findings from this mixed‐method study show that only minor elements of performance improvement get incorporated into pre‐existing compliance‐based accountability structures, that reinforcement of accountability structures works to the detriment of performance improvement intentions, and that limiting managerial influence in developing performance measures and targets diminish the utility of information for improvement. The study concludes that achieving a better balance requires an alternative to top‐down decision making that goes beyond consultation to include partnership.